The incidence of some genetic traits among junior and senior students in Alabat Municipal High School, Quezon Province, Philippines - Caparros, Leonardo Tarranco 1938- (1974)
This is a population genetic study of the ABO blood group distribution through a rapid slide technique, incidence of tongue rolling and left-right alternatives of handedness, handclasping, armfolding and leg crossing, with 331 respondents from Alabat Island, Quezon Province. Each trait studied shows no association with each other in the way it has been inherited by the samples. Likewise, the ABO blood group has no relation with any of the traits concerned.
Thesis (M.A.T.Biology)--University of the Philippines, Diliman.
Typescript.
Keywords: Trait intercorrelation; Heredity, Human; Quezon -- Students